The factors of termite (Coptotermes curvignathus) infestation and its effect on rubber industry - a review / Nor Hazami Che Abah - Che Abah, Nor Hazami (Faculty of Plantation and Agrotechnology, 2018)
The production of rubber and rubber products is a large and diverse industry. Hevea brasiliensis is the rubber crops which is termites constitute major menace to agricultural production in the tropics. The economy of any nation can be affected by the infestation of its farmlands, animal pens, residential and storage facilities by multiple termite species. This is because termites can cause denudation of farmlands, destroy growing crops, farm structures as well as the harvest in the store. The main purpose is to review the termite as a major pests of rubber crop at all the stages of rubber growth, causing reduced in rubber production. Termites as the main decomposer of organic matter in the tropical forest ecosystem are very much affected by the disturbances in their habitat. This review paper focused on the factors termite Coptotermes curvignathus infestation by environment and physical factors to maximize the productivity of the rubber. Its highlights on important factors that will contribute in its infestation which is rubber tree size and growth form, humidity and humidity factors also rubber tree condition (Immunity system of the rubber tree). Therefore, the related factors that to review will contribute in declining the production on rubber industry in our worldwide. The environmental factors are the higher contributor in termite infestation which it difficult to control rather than the physical factor where can control by cultural practices.